Service Quality of Pesantren and Its Impact on the Santri Loyalty - Ubaedullah, Dudun; Akbar, Makruf; Mukhtar, Mukhneri (International Journal for Educational and Vocational Studies, 2019)
Managing santri loyalty makes pesantren to win competition amid the high growth of pesantren in Indonesia. This study aims to examine santri loyalty model through the image of pesantren, service quality, and santri satisfaction. Samples of this study were 344 students from 2029 students of the largest pesantren in Jakarta and analyzed the data using path analysis. Findings showed that service quality of pesantren has a direct effect on santri loyalty which is the strongest compared to the image of pesantren and santri satisfaction. It is suggested to kyai and managers of pesantren can pay attention to services quality, the image of pesantren, and santri satisfaction, because it is proved to be able to increase santri loyalty.